Trends and Effectiveness of Learning Models in Improving Elementary School Students’ Explanatory Text Writing Skills: A Systematic Literature Review - Sugiarti, Dini; Nurulpaik, Iik; Sopandi, Wahyu; Rizkiah, Arni (International Conference on Elementary Education, 2025)
This study aims to analyze the trends and effectiveness of learning models used to improve explanatory text writing skills in elementary school students. This study used the Systematic Literature Review (SLR) method with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were collected from the Scopus, Web of Science, and Google Scholar databases with a publication range of 2015–2024. Of the total 120 articles identified, nine articles met the inclusion criteria and were further analyzed. The synthesis results show that constructivist-based learning models such as Project-Based Learning (PjBL), Contextual Teaching and Learning (CTL), Discovery Learning, Genre-Based Approach (GBA), and RADEC are effective in improving students' explanatory text writing skills. This effectiveness is related to the characteristics of the model, which emphasizes active engagement, collaboration, reflection, and higher-order thinking processes. This study recommends that elementary school teachers strengthen their pedagogical competencies in applying innovative learning models that are appropriate to the characteristics of students and the texts being taught.